SITUATION ANALYSIS OF CANCER MAGNITUDE IN A TERTIARY HEALTH INSTITUTION IN NIGERIA : Life Science-Pathology - ABIODUN FMCPATH, AFOLAYAN; OLATUNDE FMCPATH, IBRAHIM; FMC OBST & GYNAE, SAIDU RAKIYA; OLATUNDE FWACS, OLAOYE (International Journal of Life Science and Pharma Research, 2012)
Background: Knowledge of cancer magnitude and pattern in Nigeria is inadequate and is essentially based on estimation. The existing knowledge of cancer is based on the work of clinicians and pathologists who reported cases of cancer encountered during their professional practices. Objective: The purpose of this communication is to illustrate the magnitude and pattern of cancer at a tertiary health institution, using data generated at hospital-based cancer registry. Materials and Methods: The study involved analysis of data on new cancer cases registered at the hospital based cancer registry of University of Ilorin Teaching Hospital from 1998 to 2007. The method of data collection was by active reporting while sources of information included pathology laboratories, out-and in-patients records, radiology department and autopsy records. Primary sites (topography) of cancer were coded according to World Health Organization (WHO) International Classification of diseases 10th edition (ICD 10th). Analysis of data was by SPSS. Results: A total of 2242 new cancer cases were registered from 1998 – 2007. There were 852(38.00%) males and 1390(62.00%) females giving M: F 1:1.63. Histological verification was possible in 89.84% of cases. Breast cancer with 553 (24.67%) cases; top the list among the five commonest cancers at our centre. Others were cancer of the cervix, 328(14.63%), liver, 242(10.79%), malignant lymphoma 212(9.46%) and prostate 125(5.567%). The peak age of occurrence was the 5 th decade with 456(20.34%) cases while children accounted for 9.04% of the total new cancer cases registered. Conclusion: In other to ensure accurate and completeness of data on cancer in Nigeria, there is urgent need for establishment of a functional and properly funded population-based cancer registry at both national and state levels.